PENGARUH PENUNDAAN PENANGANAN SPUTUM TERHADAP HASIL PEMBACAAN SEDIAAN SECARA MIKROSKOPIS PADA PENDERITA TB DI UPT. LABORATORIUM KESEHATAN DAERAH PROVINSI SUMATERA UTARA - Nelma Nelma; Armida Lumbantoruan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
The background of the study is whether there are differences in the results of microscopic smear reading andthe quality of direct sputum preparations, check with sputum 24 hours at room temperature. The purpose ofthe study was to determine the effect of delaying the handling of sputum on the results of microscopicreadings of preparations in tuberculosis patients. Type of descriptive observation research. Research timeJune 2019. Research location at the Regional Health Laboratory of North Sumatra Province. The resultsshowed that from 16 sputum samples that were immediately examined, the scanty results were 2 samples, 1+there were 2 samples, 2+ there were 2 samples, 3+ there were 10 samples, whereas in the 24 hour sample atroom temperature, there were 2 negative results, 1+ there are 4, 2+ there are 3, and 3+ there are 7 samplesof BTA. Of the 16 sputum, they were immediately examined by delaying 24 hours at room temperature, 7sputum were obtained, the results of which were reduced. There is no positive number added, the samenumber of positive results is 9 sputum. This suggests that a 24-hour delay in sputum examination at roomtemperature can result in false positives. There are differences in the results between sputum directlychecked by being delayed 24 hours at room temperature 25?C. It is recommended that an AFB sputum beexamined immediately to avoid the results of false negative smear microscopic examination.